Association of serum electrolyte imbalance with tear film osmolarity in chronic dry eye syndrome - Ahmad Mustafa, Hafiz Muhammad Nasrullah, Faiza Tariq, Abdul Rafe, Junaid Afsar Khan, Muhammad Imran Ali (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Dry eye syndrome (DES) represents a multifactorial ocular surface disordercharacterised by instability of the tear film and hyperosmolarity, often reflecting systemic and local homeostatic imbalance. Recent